THE IMPACT OF INTERNET APPLICATION AS RESOURCE OF LEARNING ON STUDENTS’ INDEPENDENCE LEARNING - Budiyani, Wahyu; Sujarwo, Sujarwo (Universitas Muhammadiyah Semarang, 2019)
The purpose of this study is to (1) find out how the availability of the internet application in schools as resource of learning. (2) The effect of internet availability on students' independence learning in English lesson. The population in this study were eighth grade students of SMP N 9 Yogyakarta in 2019 as many as 36 students. Samples were taken with saturated techniques. This study used quantitative method with ex post facto research types. Data collection was carried out by interview techniques and questionnaires as data on the availability of the internet in schools as learning resources and the impact of the availability of the internet on students' independence learning in English lesson. Analysis of the data used Likert scale or called scale five. The results of this study indicate that: (1) the availability of the internet at school as a learning resource is good enough in its use and management. (2) There is a positive impact on the availability of the internet in the school as a learning resource for students' independence learning in English lesson.